2002
DOI: 10.1108/09526860210431805
|View full text |Cite
|
Sign up to set email alerts
|

Application of the balanced score‐card concept to develop a conceptual framework to measure facilities management performance within NHS facilities

Abstract: This paper discusses the application of the balanced score‐card (BSC) concept as a widely used management framework for optimal measurement of organisational performance within NHS facilities directorates and discusses the fundamental points to cover in its implementation. Thereby, the paper identifies this framework as a strategic measurement and management system for facilities management. BSC formulation within NHS estates and facilities is described as a case study based on a facilities directorate situate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 3 publications
0
46
0
3
Order By: Relevance
“…É indispensável criar ambiente favorável ao compartilhamento, não só do conhecimento inerente aos aspectos organizacionais, mas também daquele referente aos requisitos e valores humanos, que podem favorecer a internalização e a codificação do conhecimento tácito, que não é tão simples, portanto precisa ser objeto de cuidado pelas empresas, a fim de ser explorado e valorizado convenientemente. Amaratunga et al (2002), ao referirem-se às constantes mudanças no mundo dos negócios e classificá-las como geradoras de incertezas no interior das organizações, recomendam a implantação de ferramentas como o BSC -Balanced scorecard -, por exemplo, como forma de equilibrar e preservar a organização de certos riscos. Os autores enumeram, além disso, outras vantagens dessa ferramenta como apoio a um modelo de gestão, tais como ajudar a agilizar e manter a comunicação em todos os níveis, possibilitar o desenvolvimento de metas organizacionais, favorecer a criação de um sistema de recompensa e reconhecimento para a melhoria do desempenho futuro, permitir a quebra de barreiras organizacionais, apoiar a coordenação de possibilidades de crescimento, demonstrar a necessidade de melhorias de forma clara, oportunizar uma tentativa inicial realista de implementação, integrar o sistema de medida de desempenho da organização e facilitar a mudança de cultura corporativa.…”
Section: Resultsunclassified
“…É indispensável criar ambiente favorável ao compartilhamento, não só do conhecimento inerente aos aspectos organizacionais, mas também daquele referente aos requisitos e valores humanos, que podem favorecer a internalização e a codificação do conhecimento tácito, que não é tão simples, portanto precisa ser objeto de cuidado pelas empresas, a fim de ser explorado e valorizado convenientemente. Amaratunga et al (2002), ao referirem-se às constantes mudanças no mundo dos negócios e classificá-las como geradoras de incertezas no interior das organizações, recomendam a implantação de ferramentas como o BSC -Balanced scorecard -, por exemplo, como forma de equilibrar e preservar a organização de certos riscos. Os autores enumeram, além disso, outras vantagens dessa ferramenta como apoio a um modelo de gestão, tais como ajudar a agilizar e manter a comunicação em todos os níveis, possibilitar o desenvolvimento de metas organizacionais, favorecer a criação de um sistema de recompensa e reconhecimento para a melhoria do desempenho futuro, permitir a quebra de barreiras organizacionais, apoiar a coordenação de possibilidades de crescimento, demonstrar a necessidade de melhorias de forma clara, oportunizar uma tentativa inicial realista de implementação, integrar o sistema de medida de desempenho da organização e facilitar a mudança de cultura corporativa.…”
Section: Resultsunclassified
“…Modern technologies and strategic models combine financial and nonfinancial indicators to evaluate performance and link it to organizational strategy. Case studies by Lin et al (2006), Amaratunga et al (2002a), and Brackertz and Kenley (2002) have demonstrated the significant benefits of using such models on FM performance measurement. Nutt (2000) argues that a data-driven approach is necessary for FM to enhance the appropriate knowledge support provided by performance measurements.…”
Section: Case Studiesmentioning
confidence: 99%
“…Case studies with strategic models reported by Lin et al (2006), Amaratunga et al (2002a), and Brackertz and Kenley (2002) show substantial benefits for organizations, by using appropriate performance measurements for FM decisions. Lin et al (2007) have noted that data quality issues, such as differences in computing systems, lack of data integrity check, data access difficulty, lack of standards for data acquisition, organizational readiness, and lack of training, are present in most organizations.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of profession competence is the competence (attitude, knowledge and skills) that shown by professionals worker who excellent in their field of profession expertise (in construction), both technical (hard competency) and communicative (soft competency) which has a classification level of expertise consists of the new/ notice/ awareness level, the beginner/ knowledge level, the competent/ skill level, the proficient/ mastery level, and the expert level [2].…”
Section: Introductionmentioning
confidence: 99%